الخطاب الدعوي عند الشيخ علي يحي معمر دراسة استقرائية تحليلية - د. خالد سعيد تفوشيت (Sharwes Scientific Journal, 2025)
The advocacy discourse of Sheikh Ali Yahya Muammar (a critical and analytical study) In general, advocacy discourse enjoys the presence of intellectuals and common people alike in society, where they are closely present in the making of Muslims and communication across generations, and they can learn, and they can imagine life in its various diverse social, political, and political fields. The importance of this discourse can be highlighted through the advocacy efforts of Sheikh Ali Muammar, and the extent of his reliance on the authority based on the Holy Qur’an and the purified Sunnah of the Prophet, as well as by highlighting the extent of the clarity and simplicity of the sheikh’s advocacy discourse and its lack of complexity or concavity in his expressions and words. This is achieved by evaluating contemporary advocacy discourse through studying the approach followed by Sheikh Ali Muammar in calling to God by examining its mechanisms and tools. And identifying aspects of Sheikh Ali Yahya Muammar’s renewal in the preaching discourse through: his ideas and studies in the preaching and historical fields. Studying this type of discourse requires relying on a methodology based on induction, analysis, evaluation, and continuous evaluation in a way that serves and evaluates the path of those working in the advocacy field. This calls for following an approach based on dividing the research into three axes that include several branches. The first axis deals with the content of the advocacy discourse and its elements, according to Sheikh Ali Muammar. The second axis presents the advocacy discourse according to Sheikh Ali Muammar in both its theoretical and applied aspects. The third axis focuses on the mechanisms of the advocacy discourse and its tools when... Sheikh Ali Muammar.